2020
DOI: 10.1111/1759-7714.13368
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in patients with esophageal cancer or precancerous lesions assessed by EQ‐5D: A multicenter cross‐sectional study

Abstract: Background We aimed to obtain a set of health state utility scores of patients with esophageal cancer (EC) and precancerous lesions in China, and to explore the influencing factors of health‐related quality of life (HRQoL). Methods A hospital‐based multicenter cross‐sectional study was conducted. From 2013 to 2014, patients with EC or precancerous lesions were enrolled. HRQoL was assessed using a European quality of life‐5 dimension (EQ‐5D‐3L) instrument. Multivariable linear regression analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…utility index compared to other FACT-G and EQ-VAS subscale. Previous research showed that mapping studies tended to con rm the predictive ability of health utility more easily when exploring the correlation between the EQ-5D and FACT-G scales [3,32,33]. Furthermore, the SFWB was also not statistically associated with the EQ-5D utility index due to the lack of socialrelated functions [23].…”
Section: Discussionmentioning
confidence: 99%
“…utility index compared to other FACT-G and EQ-VAS subscale. Previous research showed that mapping studies tended to con rm the predictive ability of health utility more easily when exploring the correlation between the EQ-5D and FACT-G scales [3,32,33]. Furthermore, the SFWB was also not statistically associated with the EQ-5D utility index due to the lack of socialrelated functions [23].…”
Section: Discussionmentioning
confidence: 99%
“…All the items related to costs were assumed to inflate at the same inflation rate of 4.7% [ 24 ]. State-specific utilities were extracted from published papers [ 25 27 ]. A discount rate of 5% was used for both costs and effectiveness [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire consists of five dimensions, i.e., responder's mobility, self-care, usual activities, pain or discomfort, and anxiety or depression; each dimension has three response levels (1 = no problems, 2= moderate problems and 3 = extreme problems). We employed the Chinese time trade-off values for EQ-5D-3L to measure the utility values of the EQ-5D-3L [28], which has also been widely used in other studies [29,30]. The overall utility values of EQ-5D-3L ranges from -0.149 (having extreme problems) to 1 (no problems).…”
Section: Methodsmentioning
confidence: 99%